The case for prevention – Primary HIV prevention in the era of universal test and treat: A mathematical modeling study. (April 2022) - Kripke, Katharine; Eakle, Robyn; Cheng, Alison; Rana, Sangeeta; Torjesen, Kristine; Stover, John
Summary: Background: As antiretroviral therapy (ART) has scaled up and HIV incidence has declined, some have questioned the continued utility of HIV prevention. This study examines the role and cost-effectiveness of HIV prevention in the context of "universal test and treat" (UTT) in three sub-Saharan countries with generalized HIV epidemics. Methods: Scenarios were created in Spectrum/Goals models for Lesotho, Mozambique, and Uganda with various combinations of voluntary medical male circumcision (VMMC); pre-exposure prophylaxis; and a highly effective, durable, hypothetical vaccine layered onto three different ART scenarios. One ART scenario held coverage constant at 2008 levels to replicate prevention modeling studies that were conducted prior to UTT. One scenario assumed scale-up to the UNAIDS treatment goals of 90-90-90 by 2025 and 95-95-95 by 2030. An intermediate scenario held ART constant at 2019 coverage. HIV incidence was visualized over time, and cost per HIV infection averted was assessed over 5-, 15-, and 30-year time frames, with 3% annual discounting. Findings: Each prevention intervention reduced HIV incidence beyond what was achieved by ART scale-up alone to the 90-90-90/95-95-95 goals, with near-zero incidence achievable by combinations of interventions covering all segments of the population. Cost-effectiveness of HIV prevention may decrease as HIV incidence decreases, but one-time interventions like VMMC and a durable vaccine may remain cost-effective and even cost-saving as ART is scaled up. Interpretation: Primary HIV prevention is still needed in the era of UTT. Combination prevention is more impactful than a single, highly effective intervention. Broad population coverage of primary prevention, regardless of cost-effectiveness, will be required in generalized epidemic countries to eradicate HIV. Funding: This work was made possible by the generous support of the American people through the U.S. Agency for International Development (USAID) and the U.S. President's Emergency Plan for AIDS Relief (PEPFAR) through the terms of cooperative agreements 7200AA19CA00002, 7200AA19CA00003, and 7200AA21CA00011. The contents are the responsibility of the EpiC, RISE, and MOSAIC projects and do not necessarily reflect the views of USAID, PEPFAR, or the U.S. Government.